The Impact of Compilation Flags and Choosing Single- or Double-Precision Variables in Linear Systems Solvers - Brum, R. C.; de Castro, M. C. S.; Faria, C. O. (Trends in Computational and Applied Mathematics, 2023)
This paper intends to show the impact of compiler optimization flags and the variable's precision on direct methods to solve linear systems. The chosen six methods are simple direct methods, so our work could be a study for new researchers in this field. The methods are LU decomposition, LDU decomposition, Gaussian Elimination, Gauss-Jordan Elimination, Cholesky decomposition, and QR decomposition using the Gram-Schmidt orthogonalization process. Our study showed a huge difference in time between single- and double-precision in all methods, but the error encountered in the single-precision was not so high. Also, the best flags to these methods were the `-O3' and the `-Ofast' ones.